THE ROLE OF THE CIVILIZED KURDS DURING THE CENTURY (7 AH / 13 AD), THROUGH HIS BOOK (THE HISTORY OF ISLAM) - Abush, Farhad Haji; Muhammed, Ramdan Ahmed (Journal of Duhok University, 2018)
The study aims to highlight the great informationthat were provided by the Althahabi about the role of the civilized Kurds during the century (7 AH / 13 AD), through his book (The History of Islam). Althahabi considered one of the most prominent historians of  history and translations in the Levant during the Mamluk marine era. He has his own style of writing, using a unique approach combining history and translations. He was also a visionary critic, honest in conveying events and facts, and does not accept everything that is transmitted but analyzes, investigate and verifies. The study was divided in to three sections beside introduction and conclusion. The first section was devoted to talk about political and administrative positions. Among the most important positions that the Kurds hold, the prosecutor, the bailiwick, etc. While the second section focused on religious functions, and the jurists of the Kurds in the religious functions such as justice, giving advisory opinions and teaching, etc. And the third section devoted to study the role of the Kurds in scientific life, such as Quran science and science of prophet sayings and jurisprudence and asceticism.